Optimizing Noise Levels in the Inpatient Room at Bumi Panua Pohuwato Hospital - Moh. Eran; Nurmiah (Departement of Architecture, Universitas Islam Indonesia, 2023)
Bumi Panua Hospital is the only hospital in Marisa District, Pohuwato Regency. In each building, there is a lot of activity going on between patients, nurses, doctors, and visitors who arrive. In addition, the vehicle parking location which is right in front of the hospital inpatient room can cause noise which can reduce patient comfort. The noise level of the hospital must be in accordance with its function and meet health requirements, especially in inpatient rooms. The aim of this research is to carry out measurements to optimize noise levels in patient inpatient rooms at Bumi Panua Pohuwato Hospital. The method used in this research is a descriptive analysis method with a quantitative approach and acoustic simulation using the I-SIMPA application. From the results of Background Noise and Reverberation Time research on class III and II inpatient rooms at Bumi Panua District Hospital. Pohuwato. The condition of background noise in class III and II inpatient rooms is not good because the (dB) produced by background noise in the room is quite high, above 66 dB and exceeds the recommended standard regarding (dB) background noise in patient rooms. It should be below 40 - 45 dB. Based on the simulation results, the reverberation time in class III and class II inpatient rooms produces reverberation time that exceeds the recommended standard due to not using acoustic materials and the shape and volume of the room which causes sound reflection to occur for longer. Optimization is carried out to reduce the reverberation time so that the sound intensity in the room is not too long and can reduce background noise in the patient room. Keywords: Background Noise; Hospital; Reverberation Time (RT30)